Inorganic-organic chemistry : laboratory manual - Peña, Piedad C.; Garcia, Maria Rosario Virginia C. ;Saludares, Marites D. ;Navidad, Florence C. ;Villaflores, Oliver B. ;Dicioco, Christian S. (Quezon City, Philippines : C & E Publishing Inc., 2019)
The second edition highlights the principles governing tests carried out on human body fluids.
Part I. Laboratory Operations and Safety -- Part II. Laboratory Course Policies, Procedures, and Grading System -- Appendix -- References.
Includes bibliographical references.
Keywords: CHEMISTRY -- LABORATORY MANUALS